A Rare Case of an Inflammatory Myofibroblastic Tumor in a Middle-Aged Female - Lamprini Kosma; Lubna Khaldi; Panagiota Galani; Dimitrios Mytas; Sofia Lafoyianni (Case Reports in Oncological Medicine)
Inflammatory myofibroblastic tumors (IMTs) are distinct entities with specific characteristics immunohistochemically and molecularly. They are regarded as “intermediate malignancy” tumors of unknown etiology. We report a case of a 64-years-old woman with a fever and abdominal discomfort for 3 months; a computer tomography was performed indicating gastrointestinal stromal tumor. Histologically the lesion proved to be IMT of the abdomen.